Biochemical and molecular characterization of a lipase from an Algerian isolated Staphylococcus aureus strain. (18th November 2016) - Nehal, Fatima; Jallouli, Raida; Krayem, Najeh; Bou Ali, Madiha; Dilmi Bouras, Abdelkader; Fendri, Ahmed; Gargouri, Youssef
Abstract : A Staphylococcus aureus strain, isolated from an Algerian biotope, secretes a non‐induced lipase in the culture medium. The S. aureus lipase (SAL) was purified to homogeneity. Pure SAL is a monomeric protein (43 kDa). The 20 N‐terminal amino acid residues showed a high degree of homology with other staphylococcal lipase sequences. SAL presents specific activities of about 1600 and 555 U mg −1 using tributyrin and olive oil emulsion as substrates, respectively. In contrast to other staphylococcal lipases previously characterized, SAL was stable at a pH range from 6 to 9 after 1 h incubation, and retained 50% of its activity after 10 min incubation at 50 °C. The purified enzyme was also characterized using monolayer technique. Lipase activity can be measured only when the surface pressure exceeds 15 mN m −1 . The critical surface pressure ( π c ) measured with egg‐PC films was estimated at 33 mN m −1 . SAL showed a preference for the distal ester groups of the diglyceride isomers at low surface pressure, for the adjacent ester groups at high surface pressure and a preference for the sn‐3 position of the 2, 3‐ sn ‐enantiomer of dicaprin. Cloned and sequenced gene part, encoding the mature lipase shows, in comparison with S. aureus lipase 3 (SAL3), a deletion of three residues (LKA) at the N‐terminal extremity and a substitution of glycine 208 and isoleucine 226 with an arginine and leucine, respectively.